Staging Citizenship : Roma, Performance and Belonging in EU Romania. - Szeman, Ioana (Dance and performance studies., 2017)
Based on over a decade of fieldwork conducted with urban Roma, Staging Citizenship offers a powerful new perspective on one of the European Union's most marginal and disenfranchised communities. Focusing on 'performance' broadly conceived, it follows members of a squatter's settlement in Transylvania as they navigate precarious circumstances in a postsocialist state. Through accounts of music and dance performances, media representations, activism, and interactions with both non-governmental organizations and state agencies, author Ioana Szeman grounds broad themes of political economy, citizenship, resistance, and neoliberalism in her subjects' remarkably varied lives and experiences.